Beyond Adaptive Mental Functioning With Pain as the Absence of Psychopathology: Prevalence and Correlates of Flourishing in Two Chronic Pain Samples - Trompetter, Hester R.; Mols, Floortje; Westerhof, Gerben J. (Frontiers in Psychology, 2019)
Chronic pain outcomes are traditionally defined in terms of disability and illness. A definition of adaptive functioning in the context of chronic pain beyond the mere absence of negative outcomes, is the ability to flourish (i.e., experience emotional, psychological and social well-being; Keyes, 2002). We explored in two chronic pain samples the prevalence and sociodemographic, physical and psychological correlates of flourishing, and complemented this exploration with a similar examination of (being at risk for) psychopathology to help contextualize findings. Sample 1 (n = 1498) was a nationally representative sample. Subgroups included people with regular joint pain (1), regular joint pain and rheumatoid arthritis (2) and without chronic pain (3). Using chi-square tests we calculated the prevalence of both mental health outcomes and examined if people with or without chronic pain were more/less likely to flourish/at risk for psychopathology. Sample 2 (n = 238) concerned baseline data of a Randomized Controlled Trial on the effectiveness of Acceptance and Commitment Therapy for chronic pain (Trompetter et al., 2015b). We performed logistic regression analysis to identify flourishers/those at risk for depression. The Mental Health Continuum-Short Form was used to measure flourishing. The prevalence of flourishing was 34% (recurrent joint pain) and 38% (recurrent joint pain and arthritis) in sample 1, and 23% in sample 2. Compared to those without chronic pain, people with chronic pain were as likely to flourish, but more likely to be at risk for psychopathology. In sample 2, both flourishing and being at risk for depression were related foremost to psychological correlates. While engaged living was the most important correlate of flourishing, pain catastrophizing and psychological inflexibility were most important correlates of being at risk for depression. In conclusion, people with chronic pain are able to flourish. Findings suggest that positive and negative chronic pain outcomes function on two different continua, with potentially unique protective and risk factors. The Psychological Flexibility model provides pathways to explain both poor and optimal functioning in the presence of chronic pain. A better understanding of people with chronic pain who are able to flourish can be a fruitful endeavor to improve chronic pain models and interventions.